(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2026)
In recent years, the rapid development of aesthetic medicine and cosmetology has led to a significant increase in the number of cosmetological invasive procedures. Minimally invasive procedures such as botulinum therapy, contour plastic surgery, dermal fillers, mesotherapy, biorevitalization, plasmolifting, chemical peeling, laser technologies, and thread lifting have become increasingly widespread, and the scope of their application continues to expand annually. Despite being considered relatively safe, these procedures are increasingly associated with both local and systemic complications in clinical practice. In certain cases, such complications may cause serious harm to patient health, resulting in aesthetic defects, functional disorders, psycho-emotional disturbances, and even life-threatening conditions. This article analyzes the clinical, morphological, and functional characteristics of the major complications observed after cosmetological invasive procedures. In addition, the mechanisms of complication development, risk factors, forensic medical significance, and objective assessment criteria are discussed. Scientifically grounded approaches to solving the problems encountered in forensic medical evaluation of cosmetological complications are also presented.